1989/90 ネン カキ,キングジョージ トウ チョウジョウ キチ ニ オケル ニッチュウ キョウドウ カンソク ダイ 2 ネンジ - 大山, 佳邦; オオヤマ, ヨシクニ; 島田, 公夫; シマダ, キミオ; Ohyama, Yoshikuni; Shimada, Kimio (1990)
P(論文) 昭和63年度から3ヵ年計画で日中共同観測, 「大陸性南極と海洋性南極における動植物相の比較研究」が進められている。その第2年次として, 1989年12月から1990年3月まで第6次中国南極考察隊に参加してキングジョージ島の長城基地に滞在し, 陸上の微小動物を対象とした調査研究を行った。陸上の植物群落や土壌に生息する小型動物の生態学的調査として, 動物の生息場所の微気象的な観測と様々な生息場所からの標本採集を行い, また, 動物の耐寒性の研究として過冷却点や凍結融解後の生存率の測定, さらに生体成分の分析用サンプルを持ち帰った。 The collaboration between Japanese and Chinese biologists has started from the 1988/89 season with a three-year program at Great Wall Station, King George Island. Two Japanese zoologists participated in the 6th Chinese Antarctic Research Expedition for the second year, and carried out the ecological survey of terrestrial invertebrates and the study on cold-hardiness of some terrestrial arthropods. The ecological survey comprised the measurement of microclimatic conditions of moss communities and sampling of invertebrates from various habitats. An oribatid mite, a springtail and a podonomine midge were examined for the study on the cold-hardiness with respect to the adaptation to the cold climate in the Antarctic summer. departmental bulletin paper